2019
DOI: 10.1523/jneurosci.2530-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Inhibition Reveals That Processing Relative But Not Absolute Threat Requires Basal Amygdala

Abstract: While our understanding of appetitive motivation has benefited immensely from the use of selective outcome devaluation tools, the same cannot be said about aversive motivation. Findings from appetitive conditioning studies have shown that basal amygdala is required for behaviors that are sensitive to updates in outcome value, but similar results in aversive motivation are difficult to interpret due to a lack of outcome specificity. The studies reported here sought to develop procedures to isolate sensory-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These hypotheses remain speculative, and to test them, future studies must compare how selective interference with DMS and DLS pathways influence revaluation, the ability to change the outcome value of a CS in an aversive paradigm (Campese et al, 2019 ). Since changes in outcome value alter behavior when actions are goal-directed but not habit directed, interference with the DMS and DLS should alter performance if they mediate goal-directed action, and not habit action.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…These hypotheses remain speculative, and to test them, future studies must compare how selective interference with DMS and DLS pathways influence revaluation, the ability to change the outcome value of a CS in an aversive paradigm (Campese et al, 2019 ). Since changes in outcome value alter behavior when actions are goal-directed but not habit directed, interference with the DMS and DLS should alter performance if they mediate goal-directed action, and not habit action.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…Because it is more limited in the range of response options, and fewer perceptually distinct outcomes are studied, it can be difficult to isolate sensory specific encoding. However, some studies have shown that other kinds of aversive outcomes can potentially be used in a similar manner to more thoroughly probe the underlying psychology of aversive motivation (Rescorla 1974;Diaz-Mataix et al 2011;Campese et al 2019). For example, loud klaxon horns have been used as an unconditioned stimulus in previous studies of aversive PIT (Campese et al 2017a).…”
Section: Shock-avoidance Motivation Generalizes To Signals For Other mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Notwithstanding that a substantial body of research has investigated mechanisms for relative reward-value coding, 3,[10][11][12][13][14][15][16][17][18][19] we know less about how relative aversive value is computed during learning to guide appropriate value-based decisions. 5,[20][21][22][23] Reinforcement learning models propose that learning occurs when actual outcome value differs from predicted value. 24,25 This process and the error computed between actual and predicted value are driven by a valuation circuit that includes dopaminergic and GABAergic neurons.…”
Section: Introductionmentioning
confidence: 99%